Improving the measurement of food insecurity among people with HIV in South Africa: a psychometric examination. Issue 12 (26th August 2021) - Lee, Jasper S; Zopluoglu, Cengiz; Andersen, Lena S; Stanton, Amelia M; Magidson, Jessica F; Kagee, Ashraf; Joska, John A; O'Cleirigh, Conall; Safren, Steven A
Abstract: Objective: Food insecurity is a structural barrier to HIV care in peri-urban areas in South Africa (SA), where approximately 80 % of households are moderately or severely food insecure. For people with HIV (PWH), food insecurity is associated with poor antiretroviral therapy adherence and survival rates. Yet, measurement of food insecurity among PWH remains a challenge. Design: The current study examines the factor structure of the nine-item Household Food Insecurity Access Scale (HFIAS, isiXhosa-translated) among PWH in SA using a restrictive bifactor model. Setting: Primary care clinics in Khayelitsha, a peri-urban settlement in Cape Town, SA. Participants: Participants ( n 440) were PWH who received HIV care in Khayelitsha screening for a clinical trial. Most were categorised as severely ( n 250, 56·82 %) or moderately ( n 107, 24·32 %) food insecure in the past 30 d. Results: Revised parallel analysis suggested a three-factor structure, which was inadmissible. A two-factor structure was examined but did not adequately fit the data. A two-factor restrictive bifactor model was examined, such that all items loaded on a general factor (food insecurity) and all but two items loaded on one of two specific additional factors, which adequately fit the data (comparative fit index = 0·995, standardised root mean square residual = 0·019). The two specific factors identified were: anxiety/insufficient quality and no food intake. Reliability was adequate ( ω = 0·82). Conclusions: Results supported the use of a total score, and identified two specific factors of the HFIAS, which may be utilised in future research and intervention development. These findings help identify aspects of food insecurity that may drive relationships between the construct and important HIV-related variables.